Une expérience de dépôt et de classement des archives consulaires à Colmar - Kammerer, Odile (Gazette des archives, 1978)
An experience of deposit and ordening of the archives of the «Chambre de Commerce » of Colmar at the «Archives départementales » of Haut-Rhin. How the deposit was envisaged and realised ; what the cooperation was between the personnel of the Archives and the personnel of the Chambre de Commerce ; procedures and difficultes of arrangement and inventorying ; summary of the repertory.

En marge des guides d'archives - Mariotte, Jean-Yves (Gazette des archives, 1974)

Réflexions sur le préarchivage et l'archivage des dossiers de personnel - Valette, Jean (Gazette des archives, 1973)